To solve the expression \((-2)^3 \times 3^0 \times (-4)^{-2}\), we will evaluate each part step by step:
-
Calculate \((-2)^3\): \[ (-2)^3 = -2 \times -2 \times -2 = -8 \]
-
Calculate \(3^0\): \[ 3^0 = 1 \] (Any non-zero number raised to the power of 0 is 1.)
-
Calculate \((-4)^{-2}\): \[ (-4)^{-2} = \frac{1}{(-4)^2} = \frac{1}{16} \]
Now, we can substitute these values back into the original expression: \[ (-2)^3 \times 3^0 \times (-4)^{-2} = -8 \times 1 \times \frac{1}{16} \]
Next, simplify the multiplication: \[ -8 \times 1 = -8 \] Then, \[ -8 \times \frac{1}{16} = -\frac{8}{16} = -\frac{1}{2} \]
Thus, the value of the expression is: \[ \boxed{-\frac{1}{2}} \]